Terapeutic Potential of Microencapsulated Sertoli Cells in Huntington Disease. (26th May 2016) - Luca, Giovanni; Bellezza, Ilaria; Arato, Iva; Di Pardo, Alba; Mancuso, Francesca; Calvitti, Mario; Falabella, Giulia; Bartoli, Sara; Maglione, Vittorio; Amico, Enrico; Favellato, Mariagrazia; Basta, Giuseppe; et al.
Summary: Introduction: Immune dysfunction, promoted by pro‐inflammatory cytokines, plays a pivotal role in neurodegeneration associated with Huntington's disease. Aims: The aim of this study was to investigate the emerging immunoregulatory and antiinflammatory properties of Sertoli cells in Huntington's disease. Methods: The experimental R6/2 mouse model of Huntington's disease was treated by a single intraperitoneal injection of microencapsulated prepubertal porcine Sertoli cells and lifespan, motor performance and striatal inflammatory pattern have been evaluated. Results: The results of this study demonstrated that a single intraperitoneal injection of microencapsulated prepubertal porcine Sertoli cells uniquely improved performances and extended the life expectancy of R6/2 Huntington's disease mice, by immune dysfunction modulation in brain. Conclusions: This study highlights the immunomodulatory and trophic role of Sertoli cells that could be of help in the treatment of neurodegenerative disorders.